Analisis Pencampuran Jamur dengan Desain Eksperimen Menggunakan Pendekatan Fishbone Diagram di CV Budi Daya Jamur Sejati - Hermawanto, Roki; Riyanti, Iis; Sulistyowati, Enik (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Fishbone diagram analysis on oyster mushroom production at CV Budidaya Jamur Sejati which produces oyster mushroom baglog on a large scale offers more than one or two types of Baglog. To analyze defects in the production process, the fishbone diagram is very suitable for the oyster mushroom industry production process. From the fishbone diagram, it shows that production defects are caused by human factors, materials, environment, and methods. These factors include lack of supervision of raw materials, selection of seeds and inappropriate soil mixtures, poor air circulation, pest attacks, poor cleanliness, less than tight baglog arrangement, and imperfect inoculation process. Based on this analysis, the suggestions given are to increase supervision of raw materials, improve the quality of raw materials, improve cleanliness and air circulation, and improve the quality of the production process. With the implementation of these suggestions, it is hoped that CV Budidaya Jamur Sejati can improve the quality and quantity of oyster mushroom production and increase the company's competitiveness in the market